Prospects of Creating a Full-Scale Diagnostic Simulator for NPP Electric Drive Equipment - A. A. Lapkis; M. V. Kalashnikov; I. A. Mikshin (Глобальная ядерная безопасность, 2022)
The paper describes perspectives of development and manufacturing of full-scale simulator for training in methods of diagnostics of electric drive equipment used at NPPs. An approximate composition of technical means included in the simulator is given and its technical characteristics are substantiated. The training simulator of diagnostics must include an experimental stand which allows to simulate real operating conditions as well as possible defects of electric drive equipment of NPP, and also an instrumentation park and methodological support used at NPP for diagnostics. Implementation of training in methods and techniques of technical diagnostics with their practical development on the diagnostics simulator will increase the quality of diagnostic support of NPP electric drive equipment operation.